Effect of calcium chloride and floral preservatives in the vase life of gerbera cut flower - Timalsina, Sumitra; Poudel, Puspa Raj; Acharya, Anil Kumar; Pathak, Rukmagat; Pun, Umed Kumar (Nepal Agriculture Research Journal, 2023)
Postharvest loss of cut flower at all the stakeholders in Nepal before reaching consumer is about 20-25% in Nepal. The major problem in gerbera for its vase life is stem or scape bending. This study was aimed to assess the effect of calcium chloride and different floral preservatives in the vase life and to evaluate the quality of different varieties of gerbera cut flower. The study was conducted in a completely randomized design in the controlled lab of Central Agricultural Laboratory located at Hariharbhawan, Lalitpur at 17±2 ˚C temperature, 55 ± 2% relative humidity (RH) and 100 lux light. The study revealed that among two varieties, Rosalin, a light pink variety of gerbera was found to be better with prolonged vase life. Rosalin showed the longest vase life (14.05 days) with higher solution uptake (13.97 mL) and recorded minimum stem bending (43.8˚) on 15th day of vase life. Among ten different vase solutions, 4% sucrose + 1% calcium chloride (18.25 days), 4% sucrose + 0.5% calcium chloride (16.58 days) and 0.5% calcium chloride (16.25 days) were found the most effective vase solutions to prolong the vase life of gerbera cut flower as compared to control (7.67 days). Vase life solution of 4% sucrose + 1% calcium chloride is a potential commercial preservative solution to improve the keeping quality and vase life of cut gerbera. To conclude, calcium treatment along with a carbohydrate in a vase solution improves the vase life of gerbera cut flower.